Case Report: Dubin-Johnson Syndrome Presenting With Infantile Cholestasis: An Overlooked Diagnosis in an Extended Family - Naglaa M. Kamal; Omar Saadah; Hamdan Alghamdi; Ali Algarni; Mortada H. F. El-Shabrawi; Laila M. Sherief; Salma A. S. Abosabie (Frontiers Media S.A., 2022)
Dubin-Johnson syndrome (DJS) is an often-missed diagnosis of neonatal cholestasis. We report two patients with DJS, who presented with neonatal cholestasis. The first patient underwent extensive investigations for infantile cholestasis with no definitive etiology reached; the diagnosis of DJS was missed until the age of 14 years old. The diagnosis was confirmed genetically with c.2273G > T, p.G758V mutation in exon 18 of the ABCC2 gene. The 2nd patient is a 7-day-old baby, the son of the 1st patient who gave birth to him at the age of 21 years old. He was diagnosed with DJS at the age of 2 weeks based on normal clinical and laboratory workup apart from direct hyperbilirubinemia. He had the same mutation as his mother in homozygous status. The husband was heterozygous for the same mutation. DJS is one of the often-missed differential diagnoses of neonatal cholestasis. It should be suspected in patients of infantile cholestasis, who have an, otherwise, normal physical examination, and laboratory investigations to avoid unnecessary lengthy, invasive, and expensive workups.